European and national policy priorities for NEETs in the aftermath of the COVID-19 - Simões, F.; Rocca, A.; Tosun, J. (17th EACES Conference 2022/Naples, 2022)
This panel compiles a series of contributions to assess young people’s prospects in the transition from school to work in the aftermath of the COVID-19 pandemic. We will specifically offer a discussion point for (a) describing young people’s job intentions when faced with labour market demands; (b) analyzing major factors leading to a higher risk of social exclusion, with a particular focus on NEETs, and (c) assessing how decision-makers are addressing and can better match major policy instruments such as the NextGeneration to young people’s features across different countries.